New Challenges Resulting From the Loss of Function of Nav1.4 in Neuromuscular Diseases - Nicole, Sophie; Lory, Philippe (Frontiers in Pharmacology, 2021)
The voltage-gated sodium channel Nav1.4 is a major actor in the excitability of skeletal myofibers, driving the muscle force in response to nerve stimulation. Supporting further this key role, mutations in SCN4A, the gene encoding the pore-forming alpha subunit of Nav1.4, are responsible for a clinical spectrum of human diseases ranging from muscle stiffness (sodium channel myotonia, SCM) to muscle weakness. For years, only dominantly-inherited diseases resulting from Nav1.4 gain of function (GoF) were known, i.e. non-dystrophic myotonia (delayed muscle relaxation due to myofiber hyperexcitability), paramyotonia congenita and hyperkalemic or hypokalemic periodic paralyses (episodic flaccid muscle weakness due to transient myofiber hypoexcitability). These last five years, SCN4A mutations inducing Nav1.4 loss of function (LoF) were identified as the cause of dominantly and recessively-inherited disorders with muscle weakness: periodic paralyses with hypokalemic attacks, congenital myasthenic syndromes and congenital myopathies. We propose to name this clinical spectrum sodium channel weakness (SCW) as the mirror of SCM. Nav1.4 LoF as a cause of permanent muscle weakness was quite unexpected as the Na+ current density in the sarcolemma is large, securing the ability to generate and propagate muscle action potentials. The properties of SCN4A LoF mutations are well documented at the channel level in cellular electrophysiological studies However, much less is known about the functional consequences of Nav1.4 LoF in skeletal myofibers with no available pertinent cell or animal models. Regarding the therapeutic issues for Nav1.4 channelopathies, former efforts were aimed at developing subtype-selective Nav channel antagonists to block myofiber hyperexcitability. Non-selective, Nav channel blockers are clinically efficient in SCM and paramyotonia congenita, whereas patient education and carbonic anhydrase inhibitors are helpful to prevent attacks in periodic paralyses. Developing therapeutic tools able to counteract Nav1.4 LoF in skeletal muscles is then a new challenge in the field of Nav channelopathies. Here, we review the current knowledge regarding Nav1.4 LoF and discuss the possible therapeutic strategies to be developed in order to improve muscle force in SCW.